2021
DOI: 10.1111/ijd.15940
|View full text |Cite
|
Sign up to set email alerts
|

The use of intralesional corticosteroid combined with narrowband ultraviolet B in vitiligo treatment: clinical, histopathologic, and histometric evaluation

Abstract: Background Treatment of vitiligo with intralesional steroid (ILS) injections has shown to be successful in quite a few studies. It is a simple and safe treatment when used with caution with a better response in localized lesions. ObjectivesThe aim of the present study is to explore the efficacy and safety of using different concentrations of intralesional corticosteroid combined with NB-UVB phototherapy in the treatment of non-segmental vitiligo (NSV) patients.Methodology Twenty patients with non-segmental vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Good and excellent response rates were noticed in combined therapy group only. Moreover, El-Domyati et al [18] revealed that intralesional corticosteroid injections combined with NBUVB demonstrated a good and well-tolerated treatment modality in the context of vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…Good and excellent response rates were noticed in combined therapy group only. Moreover, El-Domyati et al [18] revealed that intralesional corticosteroid injections combined with NBUVB demonstrated a good and well-tolerated treatment modality in the context of vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…Эффективность сочетания глюкокортикоидов с УФБ-терапией при лечении витилиго подтверждена в исследованиях неоднократно [38][39][40]. Известно, что триамцинолон способен уменьшать прогрессирование заболевания за счёт противовоспалительного эффекта, изменения экспрессии генов, ответственных за оксидативный стресс, влияния на апоптоз клеток и функцию регуляторных Т-клеток, способствуя репигментации [41,42], а микронидлинг, в свою очередь, облегчает всасывание препарата [43].…”
Section: микронидлинг с триамцинолоном и уфб-311 нмunclassified